2022
DOI: 10.1111/are.16085
|View full text |Cite
|
Sign up to set email alerts
|

Sperm quality and nutritional condition related to management during prematuration ofLitopenaeus setiferus(F0) males

Abstract: The aim of this study was to compare management strategies for prematuration of the Litopenaeus setiferus male F0 generation through the combination of two factors, culture system and kind of food, measured in terms of sperm quality and the nutritional condition of shrimp. Four treatments were differentiated by culture system and feed (five replicates each). Treatments were clear water commercial pellet (CC), clear water fresh food (CF), biofloc commercial pellet (BC) and biofloc fresh food (BF). At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…The higher HSI, acylglycerides, and cholesterol obtained with the EP in the present study resembled results obtained in L. setiferus with commercial pellet (Barral‐Pintos & Gaxiola, 2022), but that study reported increased LPO, whereas the EP used in the present study contained vitamins sufficient to counteract this.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The higher HSI, acylglycerides, and cholesterol obtained with the EP in the present study resembled results obtained in L. setiferus with commercial pellet (Barral‐Pintos & Gaxiola, 2022), but that study reported increased LPO, whereas the EP used in the present study contained vitamins sufficient to counteract this.…”
Section: Discussionsupporting
confidence: 67%
“…In seeking a diet for male shrimps, the first step was the partial substitution of fresh food with EPs (Perez‐Velazquez et al, 2003), and recently an experimental feed has achieved a performance similar to that achieved with fresh food (Ortiz‐Guillén et al, 2022). This may reflect the quantity of macronutrients, as with the optimal protein inclusion for L. setiferus (Goimier et al, 2006); nevertheless, the amount of protein is not the sole criterion since L. setiferus can have a similar sperm quality despite different protein sources with different protein contents (Barral‐Pintos & Gaxiola, 2022). In the present work the two diets, MFF and EP, differed markedly in protein content (60% and 46%), yet the sperm quality was similar between treatments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations